The effects of sex and contraction intensity on fatigability and muscle oxygenation in trained individuals. - Kwak, Minyoung; Succi, Pasquale J.; Benitez, Brian; Mitchinson, Clara J.; Bergstrom, Haley C. (Applied Physiology, Nutrition & Metabolism, 2025)
Fatigability varies depending on sex and contraction intensity during sustained exercise. This study examined the responses of time to task failure (TTF), performance fatigability (PF), and muscle oxygenation (SmO2) in males and females during isometric handgrip holds to failure (HTF) at 30% and 60% maximum voluntary isometric contraction (MVIC). Males (n = 12) and females (n = 12) performed a pre-MVIC, handgrip HTF at randomly ordered percentages of MVIC (either 30% or 60%), followed by a post-MVIC on the dominant arm. During the HTF testing, the TTF and SmO2 responses were recorded, and PF was determined from the pre- to post-MVICs. TTF for 30% MVIC HTF was greater than 60% MVIC HTF (p < 0.001), but was not different between males and females (p = 0.117). PF exhibited an inverse relationship with intensity for each sex, while males demonstrated greater PF than females for both 30% and 60% MVIC HTF. For the 60% MVIC HTF, males demonstrated greater desaturation than females (CI95% = [−28.1, −2.6%], p = 0.021, d = 0.621), but not for the 30% MVIC HTF (CI95% = [−12.2, 7.9%], p = 0.315, d = 0.621). Sex differences in PF and SmO2 may be attributed to the differences in muscle mass, absolute strength, contractile properties, and muscle metabolism between males and females. However, these proposed differences between males and females may not fully inform exercise performance (e.g., TTF). Sex-specific fatigue responses may be affected by complex physio-psychological mechanisms, and therefore, additional investigations under diverse exercise conditions are required to better prescribe exercise for both males and females.